Jia Zhangke's 'Hometown Trilogy': Xiao Wu. - Berry, Michael (BFI film classics., 2009)
Berry's study of Jia Zhangke's masterful trilogy, Xiao Wu (1997), Platform (2000) and Unknown Pleasures offers a fascinating glimpse into the cinematic world of one of China's most influential filmmakers, and exploresÈJia'sÈconcern with themes of destruction and change, stagnation and movement, änd the ceaseless search for home.